PENINGKATAN MOTIVASI PERCAKAPAN BAHASA INGGRIS SISWA SMK WIRAKARYA MANDIRI DENGAN METODE DUBBING DAN SUBTITLING - Juliana, Juliana (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
English conversation still considered one of the skills that are difficult for students to do. Many students face difficulties when they want to communicate in English, even though students have been studying English for many years. Students often face some of the problems include the first. Students are not able to communicate with English because they do not master English vocabulary. Second, students are afraid and lacking confidence in the ability to say English vocabulary, and thirdly, there are no attractive media and learning methods to involve students communicating in English. Therefore, effective solutions are needed to motivate students to communicate in English. One solution to encourage students to interact with English is to provide new media and active learning methods. Therefore, the purpose of this community service is to improve the English conversation skills of Wirakarya Mandiri vocational students through film using dubbing and subtitling methods. The method used in the implementation of activities is lectures, discussions, and training in English conversation through film media applying subtitling and dubbing methods. The results of the event showed that there was an increase in students' knowledge and conversation skills with media through film applying dubbing and subtitling methods.